The role of acetylsalicylic acid in the prevention of thrombosis and its effect on the outcome of patients with COVID-19 - Verica Prodanović; Marijana Kovačević; Maksim Kovačević (Биомедицинска истраживања, 2025)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, was marked by a high incidence of thrombotic complications contributing to poor outcomes, particularly in hospitalized patients. Acetylsalicylic acid (ASA), known for its antiplatelet and anti-inflammatory properties, has been widely investigated for its potential role in mitigating thrombotic events associated with COVID-19. This Reviews explores the pathophysiological mechanisms linking SARS-CoV-2 infection with thrombosis and highlights the rationale for ASA use in this context. We analyze relevant clinical and observational studies, meta-analyses, and the results of the RECOVERY trial, which offer varying degrees of evidence regarding ASA effectiveness. While several retrospective studies suggest a reduction in thrombotic events, mechanical ventilation, and mortality among patients receiving lowdose ASA, randomized trials report mixed results, including a modest reduction in hospitalization duration, but no significant impact on overall mortality. Adverse events such as increased bleeding risk must also be considered. This Reviews underscores the importance of individualized risk assessment and the need for further randomized controlled trials to determine the precise role of ASA in COVID-19 management.
Keywords: acetylsalicylic acid; COVID-19; thrombosis; anticoagulation; inflammation; RECOVERY trial